Denseformer for single image deraining - Wang, Tianming; Wang, Kaige; Li, Qing (Zielona Góra: Uniwersytet Zielonogórski)
Image is one of the most important forms of information expression in multimedia. It is the key factor to determine the visual effect of multimedia software. As an image restoration task, image deraining can effectively restore the original information of the image, which is conducive to the downstream task. In recent years, with the development of deep learning technology, CNN and Transformer structures have shone brightly in computer vision.
Keywords: artificial intelligence; convolutional neural network (CNN); image deraining